자동차산업 사전제품품질계획 프로세스(APQP)의 QCDP 정량지표 적용 및 모니터링 방안 - 김혜리; 박재일 (한국설비안전학회지, 2022)
The performance measurement in the automotive parts development project is getting important because it is related to supplying quality products in a timely manner at the lowest cost by identifying changes required for customer satisfaction at an early stage and preventing late changes. The Advanced Product Quality Planning (APQP) has been adopted to improve the performance of automotive parts development projects along planning, However, these indicators such as Quality, Cost, Delivery, and Productivity (QCDPs) can not easily be monitored in comparison with their targets, which are set in the beginning of project development. In this study, we propose a performance measurement method that defines how QCDPs are measured and sets a limit of QCDPs to monitor their low performance in a timely manner in the Advanced Product Quality Planning (APQP). The effectiveness of the method is proved by applying it to an automotive part company. It will help automotive parts companies improve their project performance and corporate competitiveness in the end.
Keywords: Performance measurement; Advanced Product Quality Planning (APQP); Quality Cost Delivery and Productivity(QCDPs); Project management